A treasury of American bottles. - Ketchum, William C. (Jfrey50 (The Bobbs-Merrill Company Indianapolis / New York, 1975)
William C. Ketchum, Jr. guides us through the centuries, collecting bottles as we go--from the robust eighteenth-century wine and spirits bottles to the charming containers of the 1930s and 1940s, when glassmaking was still an art.
Keywords: Bottles - antiques. -- American